Analisis Korelasi antara Faktor Kesehatan Wilayah dan Jumlah Kasus Difteri di Kabupaten Sampang Tahun 2023 - Mesy Anggrini Putri; Mahmudah Mahmudah (Lembaga Pengembangan Kinerja Dosen, 2025)
Diphtheria is an infectious disease that is still a public health problem, including in Sampang Regency which recorded the highest number of cases in East Java Province in 2023. This study aims to analyze the relationship between several health factors that are suspected to have an effect on the number of diphtheria cases in Sampang Regency. This study uses a quantitative approach with an observational analytical design and uses secondary data from 14 sub-districts in Sampang Regency. The variables analyzed included the number of undernourished toddlers, the percentage of DPT immunization coverage, population density, the percentage of unhealthy houses, and the ratio of health facilities. The results of the Pearson correlation test showed that there were three variables that had a significant relationship with the number of diphtheria cases, namely the number of undernourished toddlers (r = 0.589; p-value = 0.027), population density (r = 0.768; p-value = 0.001), and the ratio of health facilities (r = 0.543; p-value = 0.045). Meanwhile, the variables of the percentage of DPT immunization coverage and the percentage of unhealthy houses did not show a significant relationship. These findings emphasize the importance of improving nutritional status, managing population density, and improving access to health services as a diphtheria control strategy.